Avaliação de empresas e análise de seus direcionadores de valor: um estudo de caso - Santos, José Augusto Rodrigues dos (2006)
The purpose of this paper is to analyze the relationship between the strategies implemented by the management and the growth in shareholders wealth. The case study evaluates the Makro Atacadista S/A operation, a private Brazilian branch of a multinational wholesale distributor that operates in the self-service format. The strategy of this Company is based on having an efficient cash management and maximizing its customers results. This work uses different methods of valuation. The most important is the Discounted Cash Flow (DCF) followed by economic profit, MVATM and residual profit. The conclusion presents a comparison among the calculated valuations, its equity and last market value. There is also an evaluation of its strengths and threats based on structural industry analysis theory (Porter, 1986, pg. 22)